ERGONOMIC INTERVENTION DECREASES THE LOAD OF LEARNING AND INCREASES THE STUDENTS PERFORMANCES - Pungus, Meity; Manuaba, Adnyana; Adiputra, Nyoman; Tirtayasa, Ketut (INDONESIAN JOURNAL OF BIOMEDICAL SCIENCES, 2010)
Most students’ activities in respect to the implementation of the academic curriculumare done at home. In fact, conventional activity done by the students in boardinghouse ofMinahasa tradition showed unfavorable risks to students based on the load of learning withindicators of musculoskeletal complaints, boredom, and fatigue. Consequently, thestudents were not yet able to attain the intended performance. To overcome the problems,it has made the efforts of ergonomics intervention. In order to test the capability of theergonomics interventions, it had been done a research with the hypothesis, the ergonomicsinterventions on the activity in boardinghouse of Minahasa tradition: normalizes the bodytemperature; decreases the musculoskeletal complaints; decreases the level of boredom;decreases the level of fatigue; increases the accuracy of working; increases the speed ofworking; increases the constancy of working; and increases the results of working of thestudents. This research was done in two periods by utilizing the treatment by subjectdesign. The first and second period was done during four weeks, without and withergonomic intervention. The subjects utilized in the research were as many as 15 persons.The measurements of dependent variables were done before and after doing the activity.The results of the research showed that the ergonomics interventions on the learningactivities in boardinghouse could decrease load of learning significantly (p<0.05): the bodytemperature became normal, the musculoskeletal complaints decreased 44.79%; the levelof boredom decreased 9.79%; the level of fatigue decreased 15.20%; the accuracy ofworking decreased 55.06%; the speed of working decreased 17.32%; the constancy ofworking decreased 30.72%; and the results of working of the students increased 131.44%.It can be concluded that the ergonomics interventions can: decrease the load of learning ofthe students and increase the performance of the students.